Cytological features of atypical polypoid adenomyoma of the endometrium: A case report with literature review. Issue 4 (4th February 2017) - Ebisu, Yusuke; Arimoto, Tomoko; Ishida, Mitsuaki; Miyasaka, Chika; Uemura, Yoshiko; Okada, Hidetaka; Tsuta, Koji
Abstract : Atypical polypoid adenomyoma (APA) is a rare mixed epithelial and mesenchymal tumor characterized histopathologically by the presence of disorganized hyperplastic glands with cytological atypia embedded in intersecting fascicles of fibromuscular stromal cells. Herein, we report the first documented endometrial cytological case of APA. A 35‐year‐old Japanese female presented with irregular menstrual cycles and then was found to have polypoid lesions of the endometrium. Cytological examination of the endometrium and endometrial curettage were performed. The Papanicolaou smear revealed the presence of abundant clusters of crowded glandular cells in a clean background. These clusters exhibited irregular branching and dilatation, and these glandular cells had mild to moderately enlarged round to oval nuclei. Within the dilated glands, metaplastic squamous cells (squamous morules) were observed. The most striking feature was the presence of short fascicles of the spindle cells without atypia around the dilated atypical glandular cell clusters with squamous morules. Histopathological and immunohistochemical examinations revealed a diagnosis of APA. Our report demonstrates that the characteristic cytological feature suggestive of APA is the presence of short fascicles of the spindle cells without atypia surrounding dilated atypical glandular cell clusters with squamous morules in a clean background, and their appearance can allow cytologists/cytopathologists to consider APA in differential diagnosis in the endometrial cytological specimens. Diagn. Cytopathol. 2017;45:345–349. © 2016 Wiley Periodicals, Inc.